The summer getaway - Mallery, Susan (HQN, 2022)
Jumping at the chance to visit her beloved great-aunt in California to escape her life, Robyn begins to see herself and the people she loves most with a bit more clarity, pushing her to take chances she hadn't dreamed of before.